Efficiency performance of Malaysian Islamic banks - Rossazana, Ab. Rahim; Norlina, Kadri; Farhana, Ismail (Munich University Library, 2013)
This study examines the efficiency performance of the full-fledged Islamic banks in Malaysia for the period of 2006 to 2011.The Malaysian Islamic banking industry has grown tremendously in terms of assets, deposits and total financing over the study period. Data Envelopment Analysis is employed in this study to measure the cost efficiency as well as the technical efficiency and its decompositions. The results show that, on average the main contributor of cost efficiency for Islamic domestic and foreign banks in Malaysia is allocative efficiency. In addition, the results find that Islamic foreign banks are more efficient than domestic banks with respect to pure technical efficiency and allocative efficiency.